Implementasi Pola Hidup Sehat Berbasis Keluarga - Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
A healthy lifestyle is habits and actions that support physical, mental and emotional health. The aim of this service activity is to implement a healthy, family-based lifestyle. This activity is carried out with a participatory approach involving all family members. The material presented includes the importance of balanced nutrition, environmental cleanliness and physical activity, and leaflets are also provided as a source of information for families to implement a healthy lifestyle at home. The results of the activities that have been achieved include: 1) consuming foods that are rich in nutrients, such as fruit, vegetables, whole grains, protein and healthy fats; 2) do regular exercise, such as walking, running, cycling, or other physical activity for at least 150 minutes per week; 3) ensure adequate and quality sleep, usually between 7-9 hours per night; 4) drink enough water to keep the body hydrated; 5) manage stress in healthy ways, such as hobbies; and 6) carry out regular health checks to detect health problems early.